¿Hacia los derechos de la naturaleza? Una postura ante el posible cambio de paradigma - Olivera Danos, Dante Leonardo (2025)
This paper is a literature review in which the author analyzes the possible change of paradigm in the Peruvian context with respect to considering nature or entities of nature as subjects of law. In order to do so, he begins by briefly investigating the historical and philosophical bases on the so-called “anthropocentrism” and the singularity or not of humans in nature. Then, a brief description of the anthropocentric and ecocentric positions on the relationship between humans and nature is made, which will lead us to an analysis of the implications of the philosophical bases previously analyzed in the face of the stage called constitutional state, rights, a possible ecological constitution and change. Subsequently, we will see the development of the ecological constitution at the jurisprudential level, and the care of nature at the comparative and conventional level.